Sleep in Sports: A Short Summary of Alterations in Sleep/Wake Patterns and the Effects of Sleep Loss and Jet-Lag / Schlaf im Sport: Eine kurze Zusammenfassung über Veränderungen im Schlafverhalten und den Einfluss von Schlafmangel und Jet-Lag - Kölling S (Dynamic Media Sales Verlag, 2016)
This review articleaims to summarise general aspects regarding sleep and sports. It is generally assumed that sleep is a basic requirement for physiological and psychological recovery, whereas it appears that sleep of elite athletes is highly influenced by training stimuli and external as well as internal factors. Studies about sleep deprivationand restricted sleep indicate the importance forcognitive functions as well as mood and behavioural aspects. Effects on performance parameters are not reported asconsistently. In contrast to sleep restriction, extending sleep for several nights might lead to improvements in performance, mood, and alertness. In terms ofintercontinental travel, jet-lag might be an issue for elite athletes. Although afewstudies indicate that effects on athletic performance might not be present, sleep, mood and some physiological measures are affected due to shift in time zones.Simple strategiescan be applied to enhance adaptation to the destination and diminish jet-lag symptoms.KEY WORDS: Recovery, Sleep Loss, Jet-Lag, Performance